Solid waste generation and composition at water villages in Sabah, Malaysia - Alias, Fatma Sabariah; Abdul Manaf, Latifah; Abdullah, Sabrina J. Ho; Ho Nyuk Onn@Ariffin, Mariani (Polish Journal of Environmental Studies, 2014)
Life in an estuary and at the beach are unique settlement patterns in the history of Malaysia. Sabah is well known for its water village settlements that are built on wooden pillars and which can be found along Sabah coastal water. However, a lot of problems have occurred at the Sabah water villages. Thus, the aim of this study is to measure the solid waste generation and composition in 150 households at select water villages in Sabah, Malaysia. The study was conducted at three major towns in Sabah, namely Kampung Tanjung Batu Laut, Tawau water village, Kampung Tanjung Aru, Kota Kinabalu water village and Kampung Sim-sim, Sandakan water village. Based on the results, the total waste generation is 1519.30 kg and the average solid waste generation rate per household is 0.29 kg/person/day. The main component of solid waste is food waste, which comprises 37% of the total waste generated, followed by plastic waste at 31%, paper waste 14.7%, glass 7.2%, and metal 6.3%. The remainder (3.8%) includes bulky waste, furniture, wood, etc. Although the solid waste generation rate is comparatively low, it will create a negative impact on the environment and public health if proper management of solid waste is not practiced.